Kinerja Pegawai Ditinjau dari Disiplin Kerja, Budaya Organisasi, Motivasi dan Kepuasan Kerja pada Pegawai Kecamatan Kalikotes Klaten - Kumpul Hartadi; Istiatin; Sudarwati (Indo Publishing, 2025)
In providing excellent service to the public, improving the performance of ASN must always be realized. This research phenomenon indicates symptoms of suboptimal employee performance in Kalikotes District, Klaten, several behaviors that are used as indicators such as indiscipline towards regulations, weak collaborative culture and openness, the intention to develop potential and IT skills, feeling less recognized and feeling there is no opportunity to develop. The data motivated the research aimed to examine the effects of work discipline, organizational culture, motivation, job satisfaction on employee performance. This research uses a census study, from the total population will be sampled amounting to 91 employees. Data for all constructs in this research were collected using a closed questionnaire instrument, then scored by transforming answers through a 5-point Likert-scale. Questionnaires from all variables have gone through instrument testing, followed by classical assumption testing. The method for analyzing the data is multiple linear regression and the analytical tool to prove the truth of the proposed hypothesis is the t-test. The results of the research based on the t-test analysis prove that work discipline, organizational culture, motivation, job satisfaction have a significant positive effect on employee performance. All of these predictor variables explain 38% of performance, with the remaining 62% explained by other predictors such as OCB, experience, promotions, or leadership.